The Seminoles [book with audioplayer] - Sneve, Virginia Driving Hawk (Sneve, Virginia Driving Hawk. First Americans book., 2025)
The Seminoles are known as "the people who never surrendered." As White settlers continued to encroach on their land, the Seminoles moved farther and farther into the Florida Everglades and adapted to their new environment with their hard work and ingenuity. And after defending their land in three Seminole wars, they never signed a formal peace treaty with the United States. This accessible nonfiction picture book introduces the Seminoles' early history, daily way of life, ceremonies, and more. Learn how they adapted to the Florida Everglades and their unique cultural practices, like their flat roll hairstyle and the role of an ever-burning fire in the annual Green Corn Dance. This updated edition provides the most up to date and accurate information on the Seminole people of past and present. The back of the book includes a section on Seminole life today. Author Virginia Driving Hawk Sneve grew up on the Rosebud Sioux Reservation and for over 40 years has brought the richness of Native American culture and heritage to thousands of children for over 40 years as teacher and children's book author. Her First Americans books introduce young readers to the many diverse and unique Native American nations that first called this land home.